While We Waited: Incidence and Predictors of Falls in Older Adults With Cataract - Palagyi, A.; McCluskey, P.; White, A.; Rogers, K.; Meuleners, Lynn; Ng, J.; Morlet, N.; Keay, L. (Association for Research in Vision and Ophthalmology, 2016)
Purpose: Strong evidence indicates an increased fall risk associated with cataract. Although cataract surgery can restore sight, lengthy wait times are common for public patients in many high-income countries. This study reports incidence and predictors of falls in older people with cataract during their surgical wait. Methods: Data from a prospective study of falls in adults aged ≥65 years who were awaiting cataract surgery in public hospitals in Australia were analyzed. Participants underwent assessment of vision, health status, and physical function, and recalled falls in the previous 12 months. Falls were self-reported prospectively during the surgical wait. Results: Of 329 participants, mean age was 75.7 years; 55.2% were female. A total of 267 falls were reported by 101 (30.7%) participants during the surgical wait (median observation time, 176 days): an incidence of 1.2 falls per person-year (95% confidence interval [CI] 1.0–1.3). Greater walking activity (incidence rate ratio [IRR] 1.06, 95% CI 1.01–1.10; P = 0.02, per additional hour/week), poorer health-related quality of life (IRR 1.12, 95% CI 1.05–1.20; P < 0.001, per 5-unit decrease), and a fall in the prior 12 months (IRR 2.48, 95% CI 1.57–3.93; P < 0.001) were associated with incident falls. No visual measure independently predicted fall risk. More than one-half (51.7%) of falls were injurious. Conclusions: We found a substantial rate of falls and fall injury in older adults with cataract who were awaiting surgery. Within this relatively homogenous cohort, measures of visual function alone inadequately predicted fall risk. Assessment of exposure to falls through physical activity frequency may prove valuable in identifying those more likely to fall during the surgical wait.